Engendering humanitarian support in Nigeria: a cross-sectional survey of health-related quality of life of internally displaced persons in Benue State (2020)
The humanitarian crisis which was induced by armed conflict in the North Central geo-political zone in Nigeria has assumed a tragic dimension. The crisis has forced hundreds of thousands of people to flee their homes thereby necessitating settlements in internally displaced persons camps. Benue state became the epicenter of the farmers/herdsmen crisis and the year 2018 witnessed an alarming loss of lives and properties including sacking of villages by armed militias thus necessitating IDP camps. Planning, execution and evaluation of humanitarian and health services require understanding health needs and social realities of internally displaced persons (IDPs). It was against this backdrop that the present study was designed to assess and document health related quality of life (HRQoL) of IDPs in Benue State IDP camps. A cross-sectional survey design was adopted and instrument modified from the WHOQOL-BREF. Health related quality of life was assessed using two dimensions of physical and socio-emotional health dimensions. Generated data were analysed using descriptive statistics and inferential statistics of t-test and One-Way ANOVA at 0.05 alpha level. Findings of the study showed poor health related quality of life in both dimensions. There was also significant gender difference in health related quality of life (tcal. = 4.230, df = 746, tcrit. = 1.645, p=<0.05) with female IDPs reporting lower HRQoL. The study also suggests that older respondents reported lower HRQoL than younger ones. It is concluded based on the findings of this study that HRQoL of IDPs in Benue State is significantly low and that IDPs have both poor physical, social and emotional health status. It was thus concluded that female and aged IDPs compared to male and younger IDPs face more distress. Provision of humanitarian and health support services for IDPs with specialized care for women, children and aged is strongly recommended.